Developing quantitative MRI parameters to characterize host response and tissue ingrowth into collagen scaffolds. (18th January 2019) - Shazeeb, Mohammed Salman; Howes, Stuart; Kandasamy, Sivakumar; Peiris, Thelge Buddika; Sotak, Christopher H.; Pins, George D.
Abstract : The in vivo evaluation of soft biomaterial implant remodeling routinely requires the surgical removal of the implant for subsequent histological assessment of tissue ingrowth and scaffold remodeling. This approach is very resource intensive, often destructive, and imposes practical limitations on how effectively these materials can be evaluated. MRI has the potential to non‐invasively monitor the remodeling of implanted collagen scaffolds in real time. This study investigated the development of a model system to characterize the cellular infiltration, void area fraction, and angiogenesis in collagen scaffold implants using T2 relaxation time and apparent diffusion coefficient (ADC) maps along with conventional histological techniques. Initial correlations found statistically significant relationships between the MRI and histological parameters for various regions of the implanted sponges: T2 versus cell density ( r ≈ −0.83); T2 versus void area fraction ( r ≈ +0.78); T2 versus blood vessel density ( r ≈ +0.95); ADC versus cell density ( r ≈ −0.77); and ADC versus void area fraction ( r ≈ +0.84). This suggests that MRI is sensitive to specific remodeling parameters and has the potential to serve as a non‐invasive tool to monitor the remodeling of implanted collagen scaffolds, and to ultimately assess the ability of these scaffolds to regenerate the functional properties of damaged tissues such as tendons, ligaments, skin or skeletal muscle. Abstract : For evaluating cellular responses to soft biomaterial implants, histological analyses are the current reference standard for assessing tissue ingrowth and scaffold remodeling. In this study, magnetic resonance imaging (MRI) was used to characterize the cellular infiltration, void area fraction, and angiogenesis in collagen scaffold implants using T2 relaxation time and apparent diffusion coefficient (ADC) maps. Initial correlations were found between the MRI and histological parameters suggesting that MRI is sensitive to specific remodeling parameters.